Ambulatory cancer care electronic symptom self-reporting (ACCESS) for surgical patients: a randomised controlled trial protocol. Issue 9 (17th September 2019) - Stabile, Cara; Temple, Larissa K; Ancker, Jessica S; Basch, Ethan; Carter, Jeanne; Miranda, Magen; Stein, Daniel; Stetson, Peter D; Vickers, Andrew; Simon, Brett A; Pusic, Andrea L
Abstract : Introduction: An increasing proportion of cancer surgeries are ambulatory procedures requiring a stay of 1 day or less in the hospital. Providing patients and their caregivers with ongoing, real-time support after discharge aids delivery of high-quality postoperative care in this new healthcare environment. Despite abundant evidence that patient self-reporting of symptoms improves quality of care, the most effective way to monitor and manage this self-reported information is not known. Methods and analysis: This is a two-armed randomised, controlled trial evaluating two approaches to the management of patient-reported data: (1) team monitoring, symptom monitoring by the clinical team, with nursing outreach if symptoms exceed normal limits, and (2) enhanced feedback, real-time feedback to patients about expected symptom severity, with patient-activated care as needed. Patients with breast, gynaecologic, urologic, and head and neck cancer undergoing ambulatory cancer surgery (n=2750) complete an electronic survey for up to 30 days after surgery that includes items from a validated instrument developed by the National Cancer Institute, the Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE). Information provided to patients in the Enhanced Feedback group is procedure-specific and based on updated PRO-CTCAE data from previous patients. Qualitative interviews are also performed. The primary study outcomes assess unplanned emergency department visits and symptom-triggered interventions (eg, nursing calls and pain management referrals) within 30 days, and secondary outcomes assess the patient and caregiver experience (ie, patient engagement, patient anxiety and caregiver burden). Ethics and dissemination: This study is approved by the Institutional Review Board at Memorial Sloan Kettering Cancer Center. The relationships between the study team and stakeholders will be leveraged to disseminate study findings. Findings will be relevant in designing future coordinated care models targeting improved healthcare quality and patient experience. Trial registration number: NCT03178045